The Relationship Between Parenting Patterns And Early Childhood Moral Development At TK IT Anak Cerdas Kemiling Bandar Lampung - Syahada, T. O. N.; Anggraini , H.; Hariyanto , J. (Utami Publisher, 2024)
The research is motivated by the moral development of early childhood which has not developed optimally. The purpose of this study was to determine the relationship between parenting style and early childhood moral development. This type of research is quantifiable with the type of ex post facto research. The data collection technique uses a survey method. The sampling technique uses cluster random sampling with a sample size of 27 pairs of parents and children. The results of the research show that there is a correlation of 0.286, which means that there is no high and significant positive relationship between parental parenting and the moral development of early childhood in the Kemiling Smart Children's IT Kindergarten.